Analisis Performansi Finansial Industri Batik Berdasarkan Faktor Kompetensi Industri Kecil dan Menengah (Studi Kasus: Industri Kecil dan Menengah Batik di Surakarta) - Fakhrina Fahma; Retno Wulan Damayanti; Maharani - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
SMIs Batik often unable to catch on the market opportunity that needs large production volume. Beside, SMIs batik has difficulty in the finance access and consultation. The limitation of investment also becoming a weakness for increasing the internal function. Such as training and technology inovation. In this research, there is 6 competence factors,(Financial, Human Resources, Technology and Production, Marketing, Company Management, Network and Basic Material Supply) that used to analyze the performance of SMIs Batik in Surakarta. There is 63 industries as sample.Cluster Analyze is used to grouping industries into some group. Discriminant Analyze is used to identify the discriminatory competence variable for group. The result is 63 batik industries can be grouped into 4 cluster based on 5 grouping variables: the age of company, the number of labor, company assets, omsets per year dan profit per year. With size of financial performance that is Return on Assets, Profit Margin and Sales Turnover, 4 group can be categorized as highest, high, medium and low performance of industry. 5 variables as discriminatory between 4 cluster industry that is Market Information Network, Support in Marketing, Financial Management, Operational Capability dan Promotion Activities.